2010
DOI: 10.3109/08958370903008888
|View full text |Cite
|
Sign up to set email alerts
|

Biomass smoke exposures: Health outcomes measures and study design

Abstract: Epidemiological studies of biomass smoke health effects have been conducted in a variety of settings and with a variety of study designs. The Health Effects Workgroup discussed several approaches for the investigation of health effects in communities exposed to wood smoke from nearby wildland fires, intentional agricultural burning, or residential biomass burning devices such as woodstoves or cookstoves. This presentation briefly reviews observational and intervention studies that have been conducted within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The associations between indoor air pollution exposure and specific respiratory diseases in certain age groups have been reported and reviewed descriptively1 4 11 12 and quantitatively 13–15. Previous systematic reviews and meta-analyses concluded that indoor air pollution exposure from unprocessed solid fuel use not only increases the risk of pneumonia in young children by a factor of 1.8,13 but also more than doubles the risk of COPD and CB in adults 14 15.…”
Section: Introductionmentioning
confidence: 99%
“…The associations between indoor air pollution exposure and specific respiratory diseases in certain age groups have been reported and reviewed descriptively1 4 11 12 and quantitatively 13–15. Previous systematic reviews and meta-analyses concluded that indoor air pollution exposure from unprocessed solid fuel use not only increases the risk of pneumonia in young children by a factor of 1.8,13 but also more than doubles the risk of COPD and CB in adults 14 15.…”
Section: Introductionmentioning
confidence: 99%
“…The major externalities are emissions of greenhouse gases (GHG) and black carbon. The farmers do not clearly understand the private costs of residue burning, such as health costs (Long et al 1998;Noonan and Balmes 2010) and productivity loss (Mandal et al 2004). …”
Section: Case Study Designmentioning
confidence: 99%
“…Less precipitation creates more potential for windblown dust storms (Yin et al, 2005; and allergens from drought-resistant foliage (Cahill, 2013). The frequency and intensity of wildfires are likely to increase as the climate changes (Fried et al, 2004;Littell et al, 2009;Liu et al, 2013), with documented adverse health consequences (Henderson and Johnston, 2012;Moeltner et al, 2013;Noonan and Balmes, 2010).…”
Section: Comments By John G Watson and Judith C Chowmentioning
confidence: 99%
“…Nichols et al (2013) take another look at studies focused on populations with preexisting conditions, with much the same conclusions as the CR. A large number of reviews document the adverse effects of solid fuel use in developing countries (Kodgule and Salvi, 2012;Lam et al, 2012;Noonan and Balmes, 2010;Po et al, 2011;Sumpter and Chandramohan, 2013). Some of the approaches to reducing exposure error are summarized by Baxter et al (2013).…”
Section: Comments By John G Watson and Judith C Chowmentioning
confidence: 99%